2018
DOI: 10.1158/1078-0432.ccr-17-2805
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of the PARP Inhibitor Olaparib and the WEE1 Inhibitor AZD1775 as a New Therapeutic Option for Small Cell Lung Cancer

Abstract: Introduced in 1987, platinum-based chemotherapy remains standard of care for small cell lung cancer (SCLC), a most aggressive, recalcitrant tumor. Prominent barriers to progress are paucity of tumor tissue to identify drug targets and patient-relevant models to interrogate novel therapies. Following our development of circulating tumor cell patient-derived explants (CDX) as models that faithfully mirror patient disease, here we exploit CDX to examine new therapeutic options for SCLC. We investigated the effica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 63 publications
3
97
0
Order By: Relevance
“…In addition to chemotherapy combinations, AZD1775 has shown efficacy when combined with other small molecules. Olaparib, in combination with AZD1775, demonstrated enhanced anti-tumor effects in both small cell lung and ovarian cancers [20,21]. These studies demonstrated a synergistic anti-proliferative effect, and an enhancement in apoptosis and decreases in p-CDC2 in AZD1775-treated ovarian cancer cells that was maintained in the combination.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to chemotherapy combinations, AZD1775 has shown efficacy when combined with other small molecules. Olaparib, in combination with AZD1775, demonstrated enhanced anti-tumor effects in both small cell lung and ovarian cancers [20,21]. These studies demonstrated a synergistic anti-proliferative effect, and an enhancement in apoptosis and decreases in p-CDC2 in AZD1775-treated ovarian cancer cells that was maintained in the combination.…”
Section: Discussionmentioning
confidence: 78%
“…Preliminary analysis from this ongoing study revealed that basal protein PARylation distinguishes sensitive CDX models from both intermediate and resistant models, while PARylation, like SLFN11 expression, appears to decrease with treatment and the develop-ment of resistance (72). A similar CDX-based approach investigating the combination of olaparib with or without the WEE1 inhibitor adavosertib (AZD1775) identified multiple additional biomarker candidates, including inducers and markers of replication stress, such as MYC-family proteins, phospho-RPA, and cyclinE1 (73). Given the relative dearth of tissue available in SCLC and other tumors not commonly managed via surgical resection, approaches such as these may shape the next era of biomarker discovery for PARP inhibitors and beyond.…”
Section: Predictive Biomarkers Beyond Hrdmentioning
confidence: 97%
“…This overarching mechanism of HRR restoration has been highlighted in multiple preclinical PDX studies of PARP inhibition in TNBC (15,(80)(81)(82), where functionality of HRR in virtually all cases was implied by the presence of RAD51 foci in untreated tumor samples, suggesting this could represent a useful clinical biomarker for PARP inhibitor response and/or resistance. Emerging data also suggest that these olaparibresistant cancer models can be resensitized to olaparib when combined with a WEE1 inhibitor or an ATR inhibitor (67,73,(83)(84)(85). Preclinical studies suggest that PARP inhibitor-resistant, BRCA-deficient cells have an increased reliance on ATR signaling for fork stabilization (83,84), while synthetic lethal screens identified ATR as a target that was able to overcome PARP inhibitor resistance, leading to early-phase clinical trials combining ATR and PARP inhibitors (NCT02723864, NCT03462342, NCT03682289, NCT02576444; ref.…”
Section: Ddr Inhibitor Combinationsmentioning
confidence: 99%
“…Although small‐cell lung cancer (SCLC) accounts for only 15% to 20% of all lung cancer cases, 60% of patients have extrathoracic metastases at the time of diagnosis, and few of them can survive more than 1 year, which gives a major challenge for the health care system . Despite significant progress has been done, there are still a few new small molecular drugs and biologics that have benefited patients with SCLC markedly . Thus, development of novel drugs for SCLC treatment is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Despite significant progress has been done, there are still a few new small molecular drugs and biologics that have benefited patients with SCLC markedly. 4 Thus, development of novel drugs for SCLC treatment is urgent. p53, a well-known tumor suppressor, is closely associated with diverse cellular signals involved in cell cycle, cell apoptosis, cell metabolism, and so on.…”
mentioning
confidence: 99%